Does the benefit from treating to lower blood pressure targets vary with age? A systematic review and meta-analysis. Issue 8 (August 2019) - Roush, George C.; Zubair, Ayla; Singh, Kevin; Kostis, William J.; Sica, Domenic A.; Kostis, John B.
Abstract : Background: Recommendations differ regarding how blood pressure targets should vary with age. Crucial to this controversy is whether treatment benefit varies with age. Methods: Systematic searches were conducted for trials randomizing treatment in intensive arms to the recommended SBP targets: 120–140 mmHg. Head-to-head meta-analyses and meta-regression were conducted. Results: Sixteen trials met criteria. Relative to higher targets, lower targets reduced cardiovascular events, but treatment benefit differed significantly among trials due to patient age. Treatment significantly benefited older patients (mean age 77, SD = 72–81), relative risk (RR) = 0.77 (0.61, 0.97), P = 0.025, but not younger patients (mean age 61, SD = 53–70), RR = 0.90 (0.78, 1.03), P = 0.121, even though the latter had much greater statistical power. The (RR in 80 year olds)/(RR in 55 year olds) = 0.68 (0.47, 0.97), P = 0.036. Though statistically nonsignificant, corresponding trends for more specific outcomes favored older patients: Coronary artery disease 0.80, stroke 0.85, heart failure 0.54, and total mortality 0.76. For adverse effects this trend was 0.86 (0.33, 2.26). The number needed to treat to lower targets to prevent one cardiovascular event over 10 years in eight populations declined with age by 94%+. Conclusion: In these novel results, for both RR and absolute risk, treating to SBPs of 120–140 mmHg versus higher targets benefited older patients more than younger patients without an age-related increase in the RR for adverse effects. Nonetheless, because all clinical trials excluded the most frail older patients, clinicians must consider individual patient characteristics such as frailty, autonomy, and cognitive ability when choosing blood pressure targets. Abstract : Supplemental Digital Content is available in the text